2019
DOI: 10.2139/ssrn.3313337
|View full text |Cite
|
Sign up to set email alerts
|

Capital Accumulation, Green Paradox, and Stranded Assets: An Endogenous Growth Perspective

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…In another study, Jin and Zhang (2019) show that under some conditions, environmental regulations, by directing investment toward clean capital, do not have to lead to any significant value loss resulting from stranded fossil fuel assets. Van der Ploeg and Rezai ( 2019) conduct another policy-driven simulation using a model of the global oil and gas extractive industry (without a macroeconomic model).…”
Section: Comparison With Other Estimates Of Stranded Assetsmentioning
confidence: 99%
“…In another study, Jin and Zhang (2019) show that under some conditions, environmental regulations, by directing investment toward clean capital, do not have to lead to any significant value loss resulting from stranded fossil fuel assets. Van der Ploeg and Rezai ( 2019) conduct another policy-driven simulation using a model of the global oil and gas extractive industry (without a macroeconomic model).…”
Section: Comparison With Other Estimates Of Stranded Assetsmentioning
confidence: 99%
“…If this high-carbon activity also increases the productivity of all assets, more resources are available for green investment and green capital accumulates. Climate-compatible policies may therefore exist that can drive the required clean investment without stranding high-carbon capital unnecessarily (138). Anticipation of strong near-term climate policy can also mute the green paradox effect by accelerating divestment from firms holding affected assets in the period before the policy is implemented (139).…”
Section: Political Economymentioning
confidence: 99%
“…Van der Ploeg and Rezai (2016) applied a macroeconomic model to calculate the value of stranded assets that varies with different policy scenarios. Wei Jin and ZhongXiang Zhang (2018) showed that under some conditions, environmental regulations, through directing investment towards clean capital, do not have to lead to stranding of fossil fuel assets or the Green Paradox.…”
Section: Background and The Problemmentioning
confidence: 99%